Between Motivation, Competency, And Organizational Culture: Will it Still Affecting Employee Performance If Career Development Act as Moderator? - Nanang Victor Hambali; Meirani Harsasi; Anita Maharani (Dinasti Publisher, 2025)
This study aimed to examine the factors affecting employee performance, with career development as a moderating variable. Conducted at the Regional Office of the Directorate General of Customs and Excise (Kanwil DJBC) in Aceh, the research focused on a setting with similar phenomena. A quantitative approach was employed, and data from 116 employees were analyzed using Partial Least Squares-Structural Equation Modeling (PLS-SEM). The findings revealed that organizational culture significantly influences job performance, with a coefficient of 0.423 and a p-value of 0.002. In contrast, motivation (coefficient: 0.174, p-value: 0.215) and competence (coefficient: 0.136, p-value: 0.310) did not show significant effects. Additionally, career development did not moderate the relationship between the independent variables and job performance (coefficient: 0.089, p-value: 0.482). The results emphasize the critical role of organizational culture in enhancing employee performance and suggest the need for a more structured career development framework to further support workforce effectiveness.